Pengaruh Celebrity Endorser, Label Halal dan Kualitas Terhadap Minat Beli Konsumen Produk Pasta Gigi Halal Sasha Siwak di Surakarta - Abdul Haris Romdhoni; Sumadi Sumadi; Tasya Ardhisa Firdaus (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine whether the variable celebrity endorser, halal label and quality affect the buying interest of consumers of Sasha Siwak products in Surakarta.. This research uses quantitative methods. The sampling technique used purposive sampling with a total of 75 respondents who knew the product, whether or not they had bought Sasha Siwak products in Surakarta. This study has 3 independent variables and 1 dependent variable. The results of this study indicate that the celebrity endorser variable and quality influence the consumer buying interest in Sasha Siwak's products. This is stated by t test with t count > t table, for celebrity endorser variable 4.208 > 1,99394 and quality variable 5.166 > 1,99394. The halal label variable has no effect on consumer buying interest in Sasha Siwak products, this is indicated by the value of t count < t table or -1.506 < 1,99394. In this case, the three independent variables namely celebrity endorser, halal label and quality, have a joint effect on consumers' buying interest, this is stated by the f test with a calculated f value > f table or 37.872 > 2.734